2013
DOI: 10.1186/1479-5876-11-137
|View full text |Cite
|
Sign up to set email alerts
|

Future perspectives in melanoma research. Meeting report from the “Melanoma Bridge. Napoli, December 2nd-4th 2012”

Abstract: Recent insights into the genetic and somatic aberrations have initiated a new era of rapidly evolving targeted and immune-based treatments for melanoma. After decades of unsuccessful attempts to finding a more effective cure in the treatment of melanoma now we have several drugs active in melanoma. The possibility to use these drugs in combination to improve responses to overcome the resistance, to potentiate the action of immune system with the new immunomodulating antibodies, and identification of biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 110 publications
(114 reference statements)
1
22
0
2
Order By: Relevance
“…It is worth noting that PDL‐1 expression in melanoma is extremely heterogeneous (Ascierto et al., ), with intra‐ and intertumour variability. Our finding suggests that such a variability may depend, at least in part, on the ability of melanoma to produce alternative splicing of FKBP5 gene aberrantly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that PDL‐1 expression in melanoma is extremely heterogeneous (Ascierto et al., ), with intra‐ and intertumour variability. Our finding suggests that such a variability may depend, at least in part, on the ability of melanoma to produce alternative splicing of FKBP5 gene aberrantly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple articles have been published on the prognostic and predictive value of immune infiltrates in cancer, and data collected from large cohorts of human cancer have demonstrated that the immune classification of malignant tumours adds additional information to the currently used tumour staging method (American Joint Committee on Cancer/Union for International Cancer Control tumour thickness, nodes, metastasis classification) . FOXP3 is a further candidate that may increase outcome predictions in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing and whole exome sequencing have been utilized to characterize the genomic landscape of melanoma, identifying the common genetic alterations that have led to the development of novel agents. Future translational research will no doubt improve the landscape of melanoma treatment hopefully leading to improvements in PFS and OS [103].…”
Section: Expert Commentarymentioning
confidence: 99%
“…Many have been evaluated in melanoma but remain to be clinically validated [103]. Serum levels of lactate dehydrogenase, alkaline phosphatase, melanoma inhibitory activity, tyrosinase and melana/mart1 detected by RT-PCR correlate with clinical stage and tumor progression, but only serum LDH has shown be to a strong independent prognostic factor in metastatic melanoma [103,107]. S100B has been considered a prognostic marker in stage III and IV melanoma as it relates to the tumor burden and can reflect clinical stage and progression; however, it does not provide independent prognostic information.…”
Section: Expert Commentarymentioning
confidence: 99%
See 1 more Smart Citation